Validation mutuelle des compétences dans une institution de formation d'enseignants - Philippe Ruffieux (Centre National d'Enseignement à Distance, 2017)
In 2015, the HEP Vaud launched an experimentation on mutual validation of skills (www.sqily.com), inspired by knowledge trees. It concerned the training of secondary school teachers in integrating digital technology in the classroom. This shared experience showed the advantage of offering future teachers a training model enabling them to experiment good practices, rather than simply hearing about them, and then to reproduce them in their professional posture. The recognition of skills by peers, personalized courses and practical application in the field are the main elements of a training course, the vast majority of which is given in self-study mode, and at a distance. It also shows the inevitable unforeseen events one has to face in any innovative device or the difficulties of adaptation, especially for trainers, and how they are dealt with in this context.